Spectrum of renal diseases in the pediatric population of Nepal - Nirajan Mainali; Barsha acharya; Ganesh Phulara (Journal of Pathology of Nepal)
Background: The spectrum of renal diseases varies with different ethnic populations, geographical locations and environmental factors. In children, many signs of kidney disease are either hidden or mimic other systemic diseases. There is a need of identifying renal disorders at an early stage to retard the rapid progression. This study aims to identify the different histopathological spectrum of glomerular diseases in pediatric renal biopsies.